Análise da influência de diferentes teores de materiais cimentícios suplementares em concreto - Josiane Moraes Costa (2021)
The search for increasing the durability of concrete is important to reduce maintenance costs, rehabilitation or even with demolitions of buildings that generate the need for new buildings. The partial replacement of Portland cement by supplementary cementitious materials (SCM) in concrete can contribute to a better mechanical performance and durability of the concrete structure. In addition, the use of SCM may contribute to the construction industry to reduce the environmental impact caused by the extraction of non-renewable minerals and the CO2 emission generated in the production of clinker. This work proposes to analyze the influence of different levels of supplementary cementitious materials on concrete. For this purpose, a reference dosage of usual concrete for infrastructure works was developed. From that, 9 more dosages were produced, in which Portland CPV-ARI cement was partially replaced by a certain percentage of SCM. The SCM employed will be Metacaulim, Depozo and the Red Ceramics residue, in the proportions of 5%, 10% and 20%. The mechanical characterization of the specimens occurred through the tests of compressive strength and dynamic elastic modulus. The durability parameters were evaluated using bulk electrical resistivity, water permeability, absorption, and carbonation. The results found show that the partial replacement of cement by supplementary cementitious materials can contribute to a concrete of better quality and better performance of the mechanical properties of the concrete. The compressive strength of concretes with application of Metacaulim showed an increase in relation to the reference concrete. All SCM applied significantly increased the dosage dynamic elastic modulus. In addition, the results indicate that there was a pore refinement provided by the SCM that contributed to concretes with high bulk electrical resistivity, consequently, concrete with greater durability less conducive to corrosion.